Branje - čudovito doživetje! - Kozorog Kenda, Martina (Šolska knjižnica, 2016)
For many years now, the school librarians of the Zgornje Posočje Working Group have been meeting in the working group that we established in the spring of 2009 in order to collaborate with one another and exchange examples of good practice. We, the librarians from the primary schools in Bovec, Kobarid, Tolmin and Most na Soči, have regular meetings. In the beginning of each school year, we plan activities together with which the schools will commemorate events that are important for libraries, such as October, the International School Library Month, and the International Children's Book Day on 2nd April. We agreed a few years ago that the common thread of the events would be intergenerational reading and that we would convince as many of our co-workers as possible to help to organise the events. At all of the aforementioned schools the older students read to the younger ones, and for both the experience is something special. All of the activities are organised for the purpose of demonstrating to students that reading is a wonderful experience.
Keywords: bralna pismenost; branje; motivacija; osnovne šole; šolske knjižnice